Epidemiological profile, maternal and neonatal issue of uterine rupture at the Befelatanana Obstetrics and Gynecology University Hospital - Ratsiatosika, Tanjona Andriamanetsiarivo; Randriamahavonjy, Romuald; Ravelojaona, Andry Nirina; Abasse, Baco Abdallah; Ibrahim, Housni; Rakotonirina, Ando-Miora; Rasoanandrianina, Bienvenue Solange; Andrianampanalinarivo, Rakotovao Hery (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Uterine rupture is an obstetric emergency. It involves the life of the mother and the fetus. The main objective of this study was to describe the epidemiological-clinical profile of uterine rupture in Befelatanana Obstetrics and Gynecology University Hospital from January 2016 to April 2018. Methods: This is a retrospective and descriptive study conducted from January 1, 2016 to April 30, 2018 at the Befelatanana Hospital Centre of Gynecology-Obstetrics. All pregnant patients with uterine rupture were included. Results: We recorded 35 cases of uterine rupture in 13184 deliveries with a prevalence of 2.65%. The average age was 27.69±6.21 years old. More than half of the pregnant women attended at least four prenatal care consultations. Uterine rupture occurred after a vaginal delivery attempt outside the centre in 62.86%. There were 77.14% cases occurring on non-scarred uterus and 14.29% on mechanical dystocia. A case of fetal macrosomia has been reported. There were 28.57% maternal deaths and 51.43% perinatal deaths, half of which were fetal deaths in utero and the other half were early neonatal deaths. Conclusions: Uterine rupture remains high in Madagascar. Quality antenatal care and training of the personal would be needed.